Alzheimer's disease phenotypes misdiagnosed with frontotemporal lobar degeneration: A retrospective neuropathologic study: Human neuropathology/clinico‐pathologic correlations. (7th December 2020) - Lecerf, Simon; Leroy, Melanie; Lebouvier, Thibaud; Lebert, Florence; Deramecourt, Vincent; Maurage, Claude Alain; Pasquier, Florence
Abstract: Background: Alzheimer's disease (AD) is a heterogeneous illness, with a common clinical presentation of progressive amnesia and less common « atypical » presentations which may be misdiagnosed with a pathology of the frontotemporal lobar degeneration (FTLD) spectrum. This study sought to characterize which phenotypes of AD are difficult to distinguish from FTLD. Method: Among the patients followed in the Lille Memory Clinic (France) between 1993 and 2018 and having a neuropathologic diagnosis of AD, the clinical phenotypes of those for whom there was a diagnostic hesitation between AD and FTLD (« doubt group », n = 13) were compared with the clinical phenotypes of those for whom there was no hesitation in diagnosing AD (« no doubt group », n = 40). Result: A primary progressive aphasia (PPA) phenotype and a corticobasal syndrome (CBS) phenotype are most likely to be found in the « doubt group » (PPA n = 8/13, 62, 5% ; CBS n = 2/13, 15, 4%) than in the « no doubt group » (PPA n = 1/40, 2, 5% ; CBS n = 0/40, 0%). In this study, no patient with confirmed AD fulfilled precociously the Rascovsky criteria for possible behavioural variant of frontotemporal dementia (bvFTD). Conclusion: As reported, PPA and CBS phenotypes are syndromes that can be observed in AD as in FTLD. Frontal variant of AD seems very uncommon.